System Performance Analysis of Half-Duplex Relay Network over Rician Fading Channel - Phu Tran Tin; Tran Hoang Quang Minh; Tan N. Nguyen; Miroslav Voznak (Universitas Ahmad Dahlan, 2018)
In this paper, the system performance of an amplify-and-forward (AF) relaying network over Rician Fading Channel is proposed, analyzed and demonstrated. For details this analysis, the energy and information are transferred from the source to the relay nodes by two methods: 1) time switching protocol and 2) power splitting protocol. Firstly, due to the constraint of the wireless energy harvesting at the relay node, the analytical mathematical expressions of the achievable throughput and the outage probability of both schemes were proposed and demonstrated. After that, the effect of various system parameters on the system performance is rigorously studied with closed-form expressions for the system performance. Finally, the analytical results are also demonstrated by Monte-Carlo simulation in comparison with the closed-form expressions. The numerical results demonstrated the effect of various system parameters, such as energy harvesting time, power splitting ratio, source transmission to noise power, and the threshold value, on the system performance of AF wireless relay nodes. The results show that the analytical mathematical and simulated results match for all possible parameter values for both schemes.